Upaya Meningkatkan Hasil Belajar Seni Tari SMA Negeri 3 Painan Menggunakan Metode Tutor Sebaya (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
This study aims to improve the learning outcomes of cultural arts (Dance) at SMA Negeri 3 Painan by using the peer tutor method. The type of research used is classroom action research. The instrument used in this study was in the form of a test held at the end of the cycle. Data collection techniques are carried out using observation, tests and documentation. The results showed that improving student activities and learning outcomes by using the peer tutor method in learning dance at SMA Negeri 3 Painan. It can be seen from the classical percentage of completeness of student learning outcomes in the cognitive realm increased in cycle 1, namely 83.33% with good score criteria. The results of learning students' skills (psychomotor) are also very good, judging from the classical presence of the completeness of student learning outcomes, which is 88%. Then it can be concluded that the implementation of learning with application.